Clinical influence of early follow-up glycosylated hemoglobin levels on cardiovascular outcomes in diabetic patients with ST-segment elevation myocardial infarction after coronary reperfusion. Issue 7 (November 2015) - Ahn, Jinhee; Hong, Taek Jong; Park, Jin Sup; Lee, Hye Won; Oh, Jun-Hyok; Choi, Jung Hyun; Lee, Han Cheol; Cha, Kwang Soo; Yun, Eunyoung; Jeong, Myung Ho; Chae, Shung Chull; Kim, Young Jo; et al.
<x xml:space="preserve">Abstract</x> Objective Recent studies have shown continuous control of diabetes is important for favorable outcomes in patients with ST-segment elevation myocardial infarction (STEMI). This study aimed to evaluate the clinical influence of postprocedural glycosylated hemoglobin A1c (HbA1c) levels on major adverse cardiac events (MACE) in diabetic patients with STEMI after coronary reperfusion. Patients and methods A total of 303 patients with diabetes and STEMI undergoing a primary percutaneous coronary intervention were enrolled in this study. All eligible patients were divided into the following three groups on the basis of follow-up HbA1c (FU-HbA1c) levels, which were measured at a median of 85 days after the procedure: optimal, FU-HbA1c<7%; suboptimal, 7%⩽FU-HbA1c<9%; and poor, FU-HbA1c≥9%. We analyzed the 12-month cumulative MACE, defined as mortality, nonfatal myocardial infarction, and revascularization. In addition, we investigated FU-HbA1c levels as a predictor of MACE. Results The incidence rates of MACE differed significantly between groups (6.4 vs. 13.6 vs. 19.6%; P=0.048). Moreover, the risk was increased in each successive group (hazard ratio: 1.00 vs. 2.19 vs. 3.68; P=0.046). Each 1% increase in the FU-HbA1c level posed a 26.6% relative increased risk of MACE (P=0.031). The optimal cutoff value for FU-HbA1c in predicting MACE was 7.45%. Conclusion This study showed that higher levels of early FU-HbA1c after reperfusion in diabetic patients with STEMI were associated with increased 12-month MACE, suggesting continuous serum glucose level control even after reperfusion is important for a better outcome. FU-HbA1c seems to be a useful marker for predicting clinical outcome.